Prophylaxis, diagnosis and therapy of infections in patients undergoing high-dose chemotherapy and autologous haematopoietic stem cell transplantation. 2020 update of the recommendations of the Infectious Diseases Working Party (AGIHO) of the German Society of Hematology and Medical Oncology (DGHO) - Christopeit, Maximilian Erich Joachim; Schmidt-Hieber, Martin; Sprute, Rosanne; Buchheidt, Dieter; Hentrich, Marcus; Karthaus, Meinolf; Penack, Olaf; Ruhnke, Markus; Weißinger, Florian; Cornely, Oliver Andreas; Maschmeyer, Georg (Annals of hematology, 2021)
To ensure the safety of high-dose chemotherapy and autologous stem cell transplantation (HDC/ASCT), evidence-based recommendations on infectious complications after HDC/ASCT are given. This guideline not only focuses on patients with haematological malignancies but also addresses the specifics of HDC/ASCT patients with solid tumours or autoimmune disorders. In addition to HBV and HCV, HEV screening is nowadays mandatory prior to ASCT. For patients with HBs antigen and/or anti-HBc antibody positivity, HBV nucleic acid testing is strongly recommended for 6 months after HDC/ASCT or for the duration of a respective maintenance therapy. Prevention of VZV reactivation by vaccination is strongly recommended. Cotrimoxazole for the prevention of Pneumocystis jirovecii is supported. Invasive fungal diseases are less frequent after HDC/ASCT, therefore, primary systemic antifungal prophylaxis is not recommended. Data do not support a benefit of protective room ventilation e.g. HEPA filtration. Thus, AGIHO only supports this technique with marginal strength. Fluoroquinolone prophylaxis is recommended to prevent bacterial infections, although a survival advantage has not been demonstrated.
Gesehen am 22.04.2021
Published Online: 20 October 2020